Corrosion behavior of Ti-39Nb alloy for dentistry - Fojt, Jaroslav; Joska, Ludek; Malek, Jaroslav; Sefl, Vaclav (Materials science & engineering. C, Materials for biological applications, 2015)
To increase an orthopedic implant's lifetime, researchers are now concerned on the development of new titanium alloys with suitable mechanical properties (low elastic modulus-high fatigue strength), corrosion resistance and good workability. Corrosion resistance of the newly developed titanium alloys should be comparable with that of pure titanium. The effect of medical preparations containing fluoride ions represents a specific problem related to the use of titanium based materials in dentistry. The aim of this study was to determine the corrosion behavior of β titanium alloy Ti-39Nb in physiological saline solution and in physiological solution containing fluoride ions. Corrosion behavior was studied using standard electrochemical techniques and X-ray photoelectron spectroscopy. It was found that corrosion properties of the studied alloy were comparable with the properties of titanium grade 2. The passive layer was based on the oxides of titanium and niobium in several oxidation states. Alloying with niobium, which was the important part of the alloy passive layer, resulted in no significant changes of corrosion behavior. In the presence of fluoride ions, the corrosion resistance was higher than the resistance of titanium.
Keywords: Corrosion; Surface analysis; Titanium alloy; Dental Implants; slitiny; Alloys; Impedance; Fluorides; testování materiálů; koroze; Materials Testing; Dentistry; zubní implantáty; zubní lékařství